2009
DOI: 10.1109/jqe.2009.2013116
|View full text |Cite
|
Sign up to set email alerts
|

Time-Delay Identification in a Chaotic Semiconductor Laser With Optical Feedback: A Dynamical Point of View

Abstract: International audienceA critical issue in optical chaos-based communications is the possibility to identify the parameters of the chaotic emitter and, hence, to break the security. In this paper, we study theoretically the identification of a chaotic emitter that consists of a semiconductor laser with an optical feedback. The identification of a critical security parameter, the external-cavity round-trip time (the time delay in the laser dynamics), is performed using both the auto-correlation function and dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
84
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(86 citation statements)
references
References 26 publications
2
84
0
Order By: Relevance
“…These intrinsic oscillations impose restrictions on random number generation from physical chaos [10] and raise arguments that the extracted numbers are not truly random [14]. Worse yet, the intrinsic oscillations are easily intercepted from time series [9,13] and then pose a risk of cracking to chaos systems [15].A reliable physical chaos should have a wide and flat power spectrum containing various frequency components with homogeneous amplitudes so that system's intrinsic frequencies cannot be determined. Such a chaos having a white spectrum is referred to as white chaos, which has only been founded in some mathematical maps such as the piecewise-linear Markov map [16] and the Logistic map [17].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…These intrinsic oscillations impose restrictions on random number generation from physical chaos [10] and raise arguments that the extracted numbers are not truly random [14]. Worse yet, the intrinsic oscillations are easily intercepted from time series [9,13] and then pose a risk of cracking to chaos systems [15].A reliable physical chaos should have a wide and flat power spectrum containing various frequency components with homogeneous amplitudes so that system's intrinsic frequencies cannot be determined. Such a chaos having a white spectrum is referred to as white chaos, which has only been founded in some mathematical maps such as the piecewise-linear Markov map [16] and the Logistic map [17].…”
mentioning
confidence: 99%
“…Taking the paradigm of a delay system, i.e., an ECL, as an example, the relaxation oscillation of the semiconductor laser dominates the laser intensity chaos and leads to a strong peak projecting from the power spectrum [8]. Additionally, the resonance of the external feedback cavity excites many external-cavity modes (ECMs) in the laser field and leads to a periodically modulated spectrum similar to that of a frequency comb with a spacing equal to the reciprocal of the feedback delay [9,10]. Considerable effort has recently been devoted to expand the power spectrum [8,11] or to depress the external-cavity resonances [12], but it is difficult to completely eliminate the effects of the intrinsic oscillations [3,13].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Wu et al experimentally showed that the TD signatures can be suppressed in two limits when double external cavities are used; one is that the two external cavities have roughly equal lengths, and the other is that one cavity length is approximately half of the other [11] . Rontani et al proposed that TD signature identification would be impossible when the TD is close to the relaxation period of the laser operating with weak feedback [12] . Their theory was demonstrated experimentally in 2010 [13] .…”
mentioning
confidence: 99%